Zeolite molded body

A structured zeolite body with specific pore distribution and binder composition addresses the issue of aluminum contamination in dialysis exhaust treatment, improving potassium adsorption efficiency and reducing waste generation.

JP2025015557AInactive Publication Date: 2025-01-30TOSOH CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024194866
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-16
Filing Date
2024-11-07
Publication Date
2025-01-30
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Conventional zeolite-based methods for processing dialysis exhaust solutions elute aluminum along with potassium, contaminating the solution and requiring large amounts of dialysate, which is then treated as hazardous waste.

Method used

A molded zeolite body with specific structural and compositional characteristics, including a cumulative pore distribution of 100 nm or less and a silica or zirconia binder, is used to minimize aluminum elution and enhance potassium adsorption, featuring a silica molar ratio of 3 to 100 or less (SIO2/Al2O3) and a preferred structure such as FER, HEU, or MOR.

Benefits of technology

The molded zeolite effectively suppresses aluminum elution and enhances potassium removal from dialysis exhaust solutions, achieving high adsorption capacity and selectivity for potassium while minimizing contamination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015557000001
    Figure 2025015557000001
  • Figure 2025015557000002
    Figure 2025015557000002
Patent Text Reader

Abstract

To provide at least one of a molded body containing zeolite that is capable of removing potassium from dialysis drainage while being suppressed in elution of aluminum in comparison to processing of dialysis drainage using conventional zeolite, and a potassium absorption method using the molded body.SOLUTION: A molded body includes: zeolite having an oxygen 8-membered ring structure; and at least one of a silica binder and a zirconia binder. A ratio of a cumulative pore volume of pore diameters of 10 nm or more and 100 nm or less to a cumulative pore volume of pore diameters of 5 nm or more and 300 nm or less is 25 vol.% or more and 70 vol.% or less. In addition, the molded body satisfies the following (1) or (2): (1) an average aspect ratio is 1.55 or less, and a particle diameter D50 is 200 μm or more and 600 μm or less; and (2) the average aspect ratio is greater than 1.55.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a zeolite shaped body. [Background technology]

[0002] Dialysis is a process that artificially removes waste products from blood using dialysis fluid. The waste products, mainly potassium, are removed from the blood by contacting the blood and dialysis fluid through a semipermeable membrane. A large amount of dialysis fluid is used per dialysis session, and dialysis is performed frequently. As a result, a large amount of dialysis fluid is discharged and treated as waste fluid (dialysis effluent) after dialysis. In recent years, attention has been focused on home dialysis, where dialysis patients undergo dialysis at home, from the perspective of improving quality of life, but the handling of dialysis effluent is an obstacle to its widespread use.

[0003] Meanwhile, zeolite is known as a potassium adsorbent that is easily available compared to ion exchange resins, etc. Therefore, the treatment of dialysis effluent using zeolite has been studied for the purpose of treating and regenerating the dialysis effluent.

[0004] For example, Patent Document 1 reports that dialysis effluent is treated with FAU-type zeolites with different SiO2 / Al2O3 ratios to remove potassium from the dialysis effluent and regenerate it. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] US Patent Application Publication No. 2015 / 0297815 Summary of the Invention [Problem to be solved by the invention]

[0006] However, in the treatment of dialysis effluent using zeolite as described in Patent Document 1, there was a problem that aluminum was eluted in parallel with the removal of potassium, and was mixed into the dialysis effluent.

[0007] The present disclosure is a method for treating dialysis effluent using zeolite, which reduces the amount of aluminum dissolved in the effluent. A molded body containing zeolite capable of suppressing potassium release from dialysis effluent and a molded body containing the same The present invention aims to provide at least one of a potassium adsorption method using the above-mentioned form. [Means for solving the problem]

[0008] The present inventors have focused on the structure of zeolite used for removing potassium from dialysis effluent and the form of the zeolite when used for treating the dialysis effluent. As a result, they have found that a molded body containing zeolite having a specific structure and having a controlled pore state is less susceptible to aluminum elution and exhibits excellent potassium adsorption properties.

[0009] That is, the present invention is as described in the claims, and the gist of the present disclosure is as follows. [1] A molded article comprising a zeolite having an 8-membered oxygen ring structure and at least one of a silica binder and a zirconia binder, the ratio of the cumulative pore volume of pores having diameters of 10 nm or more and 100 nm or less to the cumulative pore volume of pores having diameters of 5 nm or more and 300 nm or less is 25 vol% or more and 70 vol% or less, and the molded article satisfies the following (1) or (2).

[0010] (1) The average aspect ratio is 1.55 or less, and Particle size D50 is 200 μm or more and 600 μm or less (2) The average aspect ratio is greater than 1.55. [2] The molded body according to [1], comprising a zeolite having an 8-membered oxygen ring structure, and at least one of a silica binder and a zirconia binder, and having a cumulative pore volume ratio of pore diameters of 10 nm or more and 100 nm or less to the cumulative pore volume of pore diameters of 5 nm or more and 300 nm or less of 25 vol% or more and 70 vol% or less, and having an average aspect ratio of more than 1.55. [3] The molded body according to [1], comprising a zeolite having an 8-membered oxygen ring structure, and at least one of a silica binder and a zirconia binder, and further comprising a pore diameter of 5 nm or more and 300 nm or less, the ratio of the cumulative pore volume of the pore diameter of 10 nm or more and 100 nm or less to the cumulative pore volume of the pore diameter of 5 nm or more and 300 nm or less being 25 vol% or more and 70 vol% or less, an average aspect ratio of 1.55 or less, and a particle diameter D50 of 200 μm or more and 600 μm or less. [4] The cumulative pore area of ​​pores with diameters of 5 nm to 300 nm is 10.0 m 2 / g or more 35.0m 2 / g or less. [5] The molded article according to any one of [1] to [4], wherein the cumulative pore volume of pores having a pore diameter of 5 nm or more and 300 nm or less is 0.35 mL / g or more and 0.70 mL / g or less. [6] The molded body according to any one of [1] to [5], wherein the pore diameter at which a cumulative pore volume accounts for 50 volume% of the cumulative pore volume of pores with diameters of 5 nm or more and 300 nm or less is 75 nm or more and 160 nm or less. [7] The molded body according to any one of [1] to [6], wherein the ratio of the cumulative pore volume of pores having a diameter of 5 nm or more and 10 nm or less to the cumulative pore volume of pores having a diameter of 5 nm or more and 300 nm or less is 0.1 vol.% or more and 5.0 vol.% or less. [8] The molded body according to any one of [1] to [7], wherein the zeolite has one or more skeletal structures selected from the group consisting of FER structure, HEU structure, YFI structure, MAZ structure, CHA structure, MER structure and MOR structure. [9] The molded body according to any one of [1] to [8], wherein the molar ratio of silica to alumina in the zeolite (SiO2 / Al2O3 ratio) is 3 or more and 100 or less.

[10] A potassium adsorption method comprising the step of contacting the molded article according to any one of [1] to [9] above with a solution containing potassium ions.

[11] A column comprising the molded article described in any one of [1] to [9].

[12] A potassium adsorption system comprising the column described in

[11] . Effect of the Invention

[0011] The present disclosure makes it possible to provide at least one of a molded body containing zeolite that suppresses aluminum elution and enables potassium removal from dialysis effluent, as compared with conventional dialysis effluent treatment using zeolites, and a potassium adsorption method that uses the molded body. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present disclosure will be described below with reference to an example of an embodiment. The terms used in this embodiment are as follows. The configurations and parameters disclosed in this specification can be combined in any combination, and the upper and lower limits of the values ​​disclosed in this specification are also included in the range of any combination. The main terms used in this disclosure are as follows.

[0013] "Aluminosilicate" is a complex oxide that has a structure consisting of a repeating network of aluminum (Al) and silicon (Si) via oxygen (O). Since the number of charges in aluminum and silicon is different, for example, H + OrNa + Among aluminosilicates, those that have a crystalline XRD peak in their powder X-ray diffraction (hereinafter also referred to as "XRD") pattern are called "crystalline aluminosilicates", and those that do not have a crystalline XRD peak are called "amorphous aluminosilicates".

[0014] "Zeolite" is a compound in which the skeleton atoms (hereinafter also referred to as "T atoms") have a regular structure with oxygen (O) interposed therebetween, and the T atoms are at least one of metal atoms and / or metalloid atoms. The metal atoms can be exemplified by one or more selected from the group consisting of aluminum (Al), titanium (Ti), iron (Fe), zinc (Zn), gallium (Ga) and tin (Sn), preferably at least one of aluminum and iron, more preferably aluminum. The metalloid atoms can be exemplified by at least one selected from the group consisting of boron (B), silicon (Si), germanium (Ge), arsenic (As), antimony (Sb) and tellurium (Te), preferably silicon.

[0015] A "zeolite-like substance" is a compound having a regular structure in which T atoms are oxygen-mediated, and the T atoms contain at least an atom other than a metal or a metalloid (hereinafter also referred to as a "nonmetal atom"). An example of a nonmetal atom is phosphorus (P). Examples of zeolite-like substances include complex phosphorus compounds containing phosphorus (P) as the T atom, such as aluminophosphate (AlPO) and silicoaluminophosphate (SAPO).

[0016] The "regular structure" (hereinafter also referred to as "zeolite structure") in zeolite and zeolite-like substances is a skeletal structure specified by a structure code (hereinafter also referred to simply as "structure code") established by the Structure Commission of the International Zeolite Association. For example, the FER structure is a skeletal structure specified by the structure code "FER". The FER structure can be identified by comparing it with the XRD pattern (hereinafter also referred to as "reference pattern") described in FER of Zeolite Framework Types on the IZA Structure Commission's homepage http: / / www.iza-struture.org / databases / . With regard to the zeolite structure, the skeletal structure, the crystal structure, and the crystal phase are each used synonymously.

[0017] In the present embodiment, "-type zeolite" such as "FER type zeolite" means a zeolite having a zeolite structure of the relevant structure code, and preferably means a crystalline aluminosilicate having a zeolite structure of the relevant structure code.

[0018] The "8-membered oxygen ring structure" refers to a ring structure consisting of eight T atoms, and is also called a small pore.

[0019] The "zeolite molded body" is a composition in which powdered zeolite maintains a certain shape, and may contain not only zeolite but also at least one of a binder and a molding aid in addition to zeolite. In the present disclosure, the terms "molded body" and "zeolite molded body" are used interchangeably.

[0020] The molded body of this embodiment will be described below.

[0021] The present embodiment relates to a molded body that includes a zeolite having an 8-membered oxygen ring structure, and at least one of a silica binder and a zirconia binder, has a 10-100 nm pore volume fraction of 25 volume % or more and 70 volume % or less, and satisfies the following (1) or (2).

[0022] (1) The average aspect ratio is 1.55 or less, and Particle size D50 is 200 μm or more and 600 μm or less (2) The average aspect ratio is greater than 1.55. The molded body of this embodiment is a molded body mainly composed of zeolite, that is, a so-called zeolite molded body, and in particular, contains a zeolite having an 8-membered oxygen ring structure (hereinafter also referred to as "8-membered ring zeolite"), and at least one of a silica binder and a zirconia binder (hereinafter also referred to as "inorganic binder").

[0023] The zeolite contained in the molded body of this embodiment has an 8-membered oxygen ring structure. By having the 8-membered oxygen ring structure, potassium can easily enter the pores inside the molded body of this embodiment during the treatment of dialysis effluent, and potassium adsorbed in the zeolite is less likely to be released from the zeolite. The 8-membered ring zeolite has an ABW structure, an ACO structure, an AEI structure, an AEN structure, an AFN structure, an AFT structure, an AFX structure, an ANA structure, an APC structure, an APD structure, an ATN structure, an ATT structure, an ATV structure, an AWO structure, an AWW structure, a BCT structure, a BIK structure, a BRE structure, a CAS structure, a CDO structure, a CHA structure, a DDR structure, a DFT structure, an EAB structure, an EDI structure, an EPI structure, an ERI structure, an ESV structure, a FER structure, a GIS structure, a GME structure, a GOO structure, a HEU structure, an IHW structure, an ITE structure, an ITW structure, , JBW structure, KFI structure, LEV structure, LTA structure, LTL structure, MAZ structure, MER structure, MON structure, MOR structure, MTF structure, NSI structure, OFF structure, OWE structure, PAU structure, PHI structure, RHO structure, RTE structure, RTH structure, RWR structure, SAS structure, SAT structure, SAV structure, SIV structure, SZR structure, THO structure, TSC structure, UEI structure, UFI structure, VNI structure, YFI structure, YUG structure and ZON structure. Since the selectivity to potassium is improved by the arrangement of oxygen atoms contained in the oxygen 8-membered ring structure, the 8-membered ring zeolite is preferably a zeolite having one or more skeletal structures selected from the group of FER structure, HEU structure, YFI structure, MAZ structure, CHA structure and MOR structure, more preferably a zeolite having one or more skeletal structures selected from the group of FER structure, HEU structure, YFI structure, MAZ structure, CHA structure and MOR structure, even more preferably a zeolite having one or more skeletal structures selected from the group of FER structure, HEU structure, YFI structure and MOR structure, even more preferably a zeolite having a FER structure, HEU structure, YFI structure or MOR structure. Particularly preferred 8-membered ring zeolites include zeolites having a FER structure, MER structure or MOR structure, and further zeolites having a FER structure (FER type zeolite).

[0024] The molar ratio of silica to alumina in the 8-membered ring zeolite (SiO2 / Al2O3 ratio) is preferably 3 or more, 7 or more, 10 or more, 13 or more, or 15 or more, and 100 or less, 80 or less, 50 or less, or 35 or less. Such SiO2 / Al2O3 ratios tend to improve the potassium adsorption performance from the dialysis effluent. The upper and lower limits of the SiO2 / Al2O3 ratio may be any combination of the above, for example, 3 or more and 100 or less, 7 or more and 80 or less, or 15 or more and 35 or less.

[0025] The cationic type of the 8-membered ring zeolite is preferably at least one of cationic type: Na (sodium) and cationic type: H (proton), and more preferably cationic type: Na, in that the performance of adsorbing potassium from the dialysis effluent is likely to be improved.

[0026] The primary particle size of the 8-membered ring zeolite is preferably 0.1 μm or more and 15 μm or less.

[0027] The particle size D50 of the 8-membered ring zeolite is preferably 1 μm or more and 100 μm or less.

[0028] The molded body of the present embodiment contains an inorganic binder, and preferably contains a silica binder. By containing a silica binder as an inorganic binder, aluminum elution is likely to be reduced when the molded body comes into contact with a solution such as dialysis effluent. Furthermore, the strength of the molded body is likely to be improved by adhesion between the 8-membered ring zeolite and the silica contained in the silica binder. On the other hand, the molded body of the present embodiment may contain a zirconia binder as an inorganic binder. By adhesion between the zeolite and the zirconia contained in the zirconia binder, the strength of the molded body is likely to be improved.

[0029] The silica binder is a compound containing primarily silicon (Si) and oxygen (O), preferably a compound containing silica (SiO2), and more preferably silica.

[0030] The zirconia binder is a compound containing mainly zirconium (Zr) and oxygen (O), preferably a compound containing zirconia (ZrO2), and more preferably zirconia.

[0031] The inorganic binder contained in the molded body of the present embodiment may be either a silica binder or a zirconia binder, or may contain both of them.

[0032] The primary particle diameter of the inorganic binder is preferably 10 nm (0.010 μm) or more and 150 nm (0.150 μm) or less. In terms of promoting adhesion with zeolite, the primary particle diameter of the inorganic binder is more preferably 10 nm (0.010 μm) or more and 20 nm (0.020 μm) or less. On the other hand, in terms of preventing elution into dialysis effluent, the primary particle diameter of the inorganic binder is more preferably 70 nm (0.070 μm) or more and 120 nm (0.120 μm) or less.

[0033] The particle size D50 of the silica binder is preferably 15 μm or more and 40 μm or less, and the particle size D50 of the zirconia binder is preferably 0.05 μm or more and 40 μm or less.

[0034] The particle size of the 8-membered ring zeolite and the particle size D50 of the inorganic binder are both particle sizes corresponding to the D50 (median size) of the volumetric particle size distribution obtained by the laser diffraction / scattering method using a general particle size distribution measuring device (e.g., device name: MT-3100II, manufactured by Microtrack Bell).

[0035] The molded body of the present embodiment is likely to improve the potassium adsorption property while maintaining the strength of the molded body. Therefore, it is preferable that the mass of the inorganic binder is 10 parts by mass or more, 15 parts by mass or more, or 20 parts by mass or more, and 40 parts by mass or less, 30 parts by mass or less, or 25 parts by mass or less, relative to 100 parts by mass of the 8-membered ring zeolite (anhydrous equivalent mass). For example, if the inorganic binder is 10 parts by mass or more and 40 parts by mass or less, 15 parts by mass or more and 30 parts by mass or less, or 20 parts by mass or more and 25 parts by mass or less, relative to 100 parts by mass of the 8-membered ring zeolite (anhydrous equivalent mass), the amount of aluminum elution is likely to be reduced.

[0036] The anhydrous masses of the 8-membered ring zeolite and the inorganic binder are the masses after heat treatment at 600°C for 1 hour in the air, and the anhydrous mass of the molding aid is the mass after heat treatment at 80°C for 1 hour in the air.

[0037] The molded body of the present embodiment preferably contains zeolite having an 8-membered oxygen ring structure, and at least one of a silica binder and a zirconia binder, and the ratio of the cumulative pore volume of pores having diameters of 10 nm to 100 nm to the cumulative pore volume of pores having diameters of 5 nm to 300 nm is 25 vol% to 70 vol%, and the average aspect ratio is more than 1.55. By satisfying such an average aspect ratio, the molded body exhibits high potassium adsorption performance regardless of the particle diameter D50.

[0038] Since an increased external surface area of ​​the molded article increases the contact area with the dialysis fluid, the average aspect ratio is preferably more than 1.55, more preferably more than 1.55 and 2.70 or less, even more preferably 1.60 or more and 2.60 or less, and even more preferably 1.80 or more and 2.55 or less.

[0039] In this embodiment, the "aspect ratio" of the molded body is a value represented by the ratio of the long diameter to the short diameter of the molded body, and the "average aspect ratio" is the average value of the aspect ratio. The long diameter and short diameter of the molded body may be defined as the long side [μm] and the short side [μm] of a rectangle circumscribing the molded body image obtained when the molded body observed independently is projected onto the same plane in scanning electron microscope (hereinafter also referred to as "SEM") observation. Therefore, the "aspect ratio" is 1.00 or more. SEM observation may be performed using a general scanning electron microscope (for example, device name: JSM-IT200, manufactured by JEOL Ltd.) under the following conditions.

[0040] Acceleration voltage: 6kV Magnification: 30±10x The average aspect ratio of the molded article of this embodiment may be calculated as the arithmetic mean of the aspect ratios of 50±5 molded articles observed by the above method.

[0041] The molded body of this embodiment has an average short diameter of preferably 150 μm to 700 μm, more preferably 200 μm to 650 μm, and even more preferably 400 μm to 650 μm. The "average short diameter" of the molded body is the average value of the short diameters of the molded bodies, and is calculated by arithmetic mean of the short diameters of 50±5 molded bodies observed by the same method as above through SEM observation.

[0042] The molded body of the present embodiment may include a zeolite having an 8-membered oxygen ring structure, and at least one of a silica binder and a zirconia binder, and may have a cumulative pore volume ratio of pore diameters of 10 nm or more and 100 nm or less to the cumulative pore volume of pore diameters of 5 nm or more and 300 nm or less of 25 volume% or more and 70 volume% or less, an average aspect ratio of 1.55 or less, and a particle diameter D50 of 200 μm or more and 600 μm or less.

[0043] When the average aspect ratio is 1.55 or less, the contribution of the particle diameter D50 to the potassium adsorption performance becomes large. By combining such an average aspect ratio and particle diameter D50, the potassium adsorption performance tends to be high. In terms of facilitating the improvement of the packing density of the molded body, the average aspect ratio is preferably more than 1.00 and 1.55 or less, and more preferably 1.30 or more and 1.50 or less.

[0044] When the average aspect ratio of the molded body of this embodiment is 1.55 or less, its particle size D50 is 200 μm or more and 600 μm or less. If the particle size D50 of the molded body is less than 200 μm, the flow rate of the dialysis effluent, etc. will be slow. On the other hand, if the particle size D50 exceeds 600 μm, the molded body itself will be too large. As a result, the dialysis effluent will not easily penetrate into the molded body, and the efficiency of potassium removal from the dialysis effluent will be too low. The particle size D50 of the molded body of this embodiment is preferably 250 μm or more, 300 μm or more, or 350 μm or more, and 550 μm or less, 500 μm or less, or 450 μm or less. The upper and lower limits of the particle diameter D50 may be any combination of the above. For example, if the particle diameter D50 is 250 μm or more and 550 μm or less, 300 μm or more and 500 μm or less, or 350 μm or more and 450 μm or less, the amount of aluminum elution is easily suppressed without deteriorating the potassium adsorption characteristics.

[0045] The particle size D50 of the molded body is the particle size corresponding to the D50 (median size) of the volumetric particle size distribution obtained by the laser diffraction / scattering method using a general particle size distribution measuring device (for example, the device name: MT-3100II, manufactured by Microtrack Bell). Specific measurement conditions include the following.

[0046] Pretreatment: Dry in air at 110℃ for 1 hour Measurement range: 0.7 to 1000 μm Transparency: Transparent Shape: Non-spherical Refractive index: 1.66 Atmosphere: Air (dry) Solvent refractive index: 1 The ratio of the cumulative pore volume of pores having a diameter of 10 nm to 100 nm to the cumulative pore volume of pores having a diameter of 5 nm to 300 nm (hereinafter also referred to as the "total pore volume") of the molded body of this embodiment is 25 vol% to 70 vol%. If the pore volume ratio of 10-100 nm of the molded body is less than 25 vol%, the potassium adsorption capacity is likely to decrease, and if it exceeds 70 vol%, other ions are likely to be adsorbed, and the potassium selectivity is likely to decrease. The pore volume ratio of 10-100 nm of the molded body of this embodiment is 30 vol% or more, 33 vol% or more, 43 vol% or more, or 53 vol% or more, and is preferably 69 vol% or less, 67 vol% or less, or 65 vol% or less. The upper and lower limits of the 10-100 nm pore volume fraction may be any combination of the above, for example, 25 vol.% or more and 70 vol.% or less, 30 vol.% or more and 70 vol.% or less, 33 vol.% or more and 69 vol.% or less, 43 vol.% or more and 67 vol.% or less, or 53 vol.% or more and 65 vol.% or less.

[0047] The cumulative pore area (hereinafter also referred to as the "total pore area") of the molded body of this embodiment having a pore diameter of 5 nm or more and 300 nm or less is 10.0 m 2 / g or more, 20.0m 2 / g or more or 25.0m 2 / g or more, and 35.0m 2 / g or less or 32.0m 2 The upper and lower limits of the total pore area may be any combination of the above, for example, 10.0 m 2 / g or more 35.0m 2 / g or less, 20.0m 2 / g or more 35.0m 2 / g or less, or 25.0m 2 / g or more 32.0m 2 / g or less is sufficient.

[0048] The total pore volume of the molded body of this embodiment is preferably 0.35mL / g or more, 0.36mL / g or more, or 0.38mL / g or more, and 0.70mL / g or less, 0.60mL / g or less, 0.50mL / g or less, 0.48mL / g or less, or 0.45mL / g or less. The upper and lower limits of the total pore volume may be any combination of the above, for example, 0.35mL / g or more and 0.70mL / g or less, 0.35mL / g or more and 0.60mL / g or less, 0.35mL / g or more and 0.50mL / g or less, 0.36mL / g or more and 0.60mL / g or less, 0.36mL / g or more and 0.50mL / g or less, 0.36mL / g or more and 0.48mL / g or less, or 0.38mL / g or more and 0.45mL / g or less.

[0049] The combination of the total pore area and the total pore volume, and the upper and lower limits of each of them may be any combination as described above. The total pore area is, for example, 10.0 m 2 / g or more 35.0m 2 / g or less, 20.0m 2 / g or more 32.0m 2 / g or less, or 25.0m 2 / g or more 32.0m 2 The upper and lower limits of the total pore volume may be any combination of the above, and examples thereof include 0.35 mL / g or more and 0.50 mL / g or less, 0.36 mL / g or more and 0.48 mL / g or less, and 0.38 mL / g or more and 0.45 mL / g or less.

[0050] When the total pore area or total pore volume is within the above range, the dialysis effluent can easily permeate into the molded article, and as a result, the potassium adsorption performance can easily be improved.

[0051] In the molded body of this embodiment, the pore diameter at which the cumulative pore volume relative to the total pore volume is 50% (hereinafter also referred to as "pore diameter D50") is preferably 75 nm or more and 160 nm or less. The pore diameter D50 is 76 nm or more, 80 nm or more, or 100 nm or more, and more preferably 155 nm or less, 120 nm or less, 118 nm or less, 116 nm or less, or 114 nm or less. The upper and lower limits of the pore diameter D50 may be any combination of the above, and the pore diameter D50 may be, for example, 76 nm or more and 160 nm or less, 80 nm or more and 160 nm or less, 100 nm or more and 155 nm or less, 75 nm or more and 155 nm or less, 75 nm or more and 120 nm or less, 76 nm or more and 118 nm or less, 80 nm or more and 116 nm or less, or 100 nm or more and 114 nm or less.

[0052] When the pore diameter D50 is within the above range, the potassium adsorption performance tends to be higher.

[0053] The ratio of the cumulative pore volume of pores with a diameter of 5 nm to 10 nm to the total pore volume of the molded body of this embodiment (hereinafter also referred to as "5-10 nm pore volume ratio") is preferably 0.1 volume% to 5.0 volume%. The 5-10 nm pore volume ratio is preferably 1.5 volume% or more, 2.2 volume% or more, or 3.1 volume% or more, and 4.9 volume% or less, 4.1 volume% or less, or 3.7 volume% or less. When the 5-10 nm pore volume ratio is the above ratio, potassium adsorption tends to be fast. The upper and lower limits of the 5-10 nm pore volume ratio may be any combination of the above, for example, 1.5 volume% to 4.9 volume%, 2.2 volume% to 4.1 volume%, or 3.1 volume% to 3.7 volume%.

[0054] The pore area, pore volume and pore diameter of the molded body can be measured by mercury intrusion porosimetry in accordance with JIS Z 1655. Specific measurement conditions include the following.

[0055] Sample mass: 0.10g Mercury introduction pressure: 601.6psia~36,098.1psia (4.1MPa~248.9MPa) Measuring pore diameter: 5nm~300nm Cell used: Pressed volume 1.1cc glass cell Mercury surface tension: 480dyn Mercury contact angle: 130° Pretreatment conditions: Degassing in air at 110℃ for 1 hour or more (1 hour or more, 3 hours or less) For the measurement, a general mercury porosimeter (for example, device name: Autopore 9510, manufactured by Micromeritics) may be used.

[0056] The bulk density of the molded body of this embodiment is 0.1 g / cm 3 More than 0.65g / cm 3 It is preferable that the bulk density is 0.1 g / cm or less. 3 If the bulk density is 0.65 g / cm or more, the molded product becomes easy to handle. 3 If the bulk density is 0.1 g / cm or less, the flow of the dialysis waste fluid is not excessively hindered and high packing property is easily exhibited. 3 More than 0.2g / cm 3 or more than 0.3g / cm 3 More than 0.65g / cm 3 Below 0.60g / cm 3 Less than or equal to 0.58g / cm 3 The upper and lower limits of the bulk density may be any combination of the above, for example, 0.1 g / cm 3 More than 0.65g / cm 3 Below, 0.2g / cm 3 More than 0.60g / cm 3 Less than or equal to 0.3g / cm 3 More than 0.58g / cm 3 The following is acceptable.

[0057] The molded product of the present embodiment can be formed into a desired shape suitable for the purpose. The shape of the molded product of the present embodiment can be one or more selected from the group consisting of a cylindrical shape, a pellet shape, a bead shape, a substantially spherical shape, and a ring shape, and further can be at least one of a cylindrical shape and a bead shape, and can be any shape depending on the application.

[0058] The molded article of the present embodiment is suitable for removing potassium from dialysis effluent. For example, the potassium (K + The removal rate is preferably 20% or more, 30% or more, or 40% or more, and 100% or less, 99% or less, or 98% or less. The simulated adsorption evaluation may be performed as follows: That is, an aqueous solution containing KCl, NaCl, MgCl2, and CaCl2 and having the following composition is prepared as a simulated dialysis solution.

[0059] K: 1.0mEq / L Na: 132.0 mEq / L Magnesium: 0.5 mEq / L Ca: 3.5 mEq / L Next, 2.5 mL of the molded article of this embodiment is packed into a glass column with an inner diameter of 8.4 mm, and the simulated dialysis solution is passed through the glass column at a flow rate of 100 mL / min. A total of 500 mL of the simulated dialysis solution discharged from the glass column is collected every 100 mL from the start of discharge, and each is diluted 10 times with pure water to prepare a measurement solution. The potassium, calcium, and magnesium concentrations of the measurement solution obtained by ICP atomic emission spectrometry using a general ICP-AES device (e.g., OPTIMA3000DV, manufactured by PERKIN-ELMER) are measured, and then the potassium removal rate can be calculated from the following formulas (1) and (2).

[0060] Potassium removal rate [%] = (A1 + A2 + A3 + A4 + A5) / 5 × 100 (1) In formula (1), A1 to A5 are the potassium removal rates [%] of each measurement solution.

[0061] Potassium removal rate of each test solution [%] = (C0-Cn) / C0×100 (2) In equation (2), C0 is the potassium concentration of the simulated dialysis fluid [1.0 mEq / L], and Cn is the potassium concentration in each measurement solution [mEq / L].

[0062] Prior to the simulated adsorption evaluation, the molded body of this embodiment may be pretreated by mixing it with 1 L of an aqueous sodium chloride solution having a NaCl concentration of 10 mass % and then washing it with 1.5 L of pure water.

[0063] In the simulated adsorption evaluation, the magnesium removal rate and calcium removal rate are preferably lower than the potassium removal rate. For example, magnesium (Mg 2+ ) removal rate is 15% or less, 10% or less, or 6% or less. On the other hand, calcium (Ca 2+ ) The removal rate may also be 15% or less, 10% or less, or 6% or less.

[0064] The lower limit of the magnesium removal rate and the calcium removal rate can be, for example, 0% or more, 0.5% or more, or 1.0% or more, respectively.

[0065] However, the calcium removal rate or magnesium removal rate can be calculated by converting potassium in the above formulas (1) and (2) into calcium or magnesium.

[0066] The molded article of the present embodiment has low aluminum elution when it comes into contact with a solution such as dialysis effluent, etc. For example, the molded article of the present embodiment has an aluminum elution amount of 0.01 ppm by mass or more and 0.50 ppm by mass or less, 0.01 ppm by mass or more and 0.20 ppm by mass or less, or 0.01 ppm by mass or more and 0.15 ppm by mass or less in the following aluminum elution evaluation.

[0067] For the evaluation of aluminum elution, 1 mL of the molded body of the present embodiment is mixed with 10 mL of pure water, and then the mixture is shaken under conditions of 37°C, 6 hours, and 1.0±0.5 Hz. After shaking, the supernatant is filtered through a membrane filter to obtain a measurement solution. The aluminum content of the measurement solution is measured by ICP atomic emission spectrometry using an ICP-AES (product name: OPTIMA3000DV, manufactured by PERKIN-ELMER), and this is taken as the amount of aluminum elution.

[0068] Prior to the evaluation of aluminum elution, the measurement sample may be pretreated by mixing it with 1 L of an aqueous sodium chloride solution with a NaCl concentration of 10 mass % and then washing it with 1.5 L of pure water.

[0069] The amount of aluminum elution in the above-mentioned aluminum elution evaluation is preferably small, and may be, for example, 0 ppm by mass or more or 0.01 ppm by mass or more.

[0070] The molded article of the present embodiment is suitable for removing potassium from dialysis effluent, but may also be used in a potassium adsorption method that includes a step of contacting a solution containing potassium ions.

[0071] Furthermore, the molded article of the present embodiment may be used as an adsorbent for selectively removing potassium from a solution containing at least two kinds of alkali metal ions and alkaline earth metal ions. The molded article of the present embodiment can be used as an adsorbent for potassium, further as an adsorbent for potassium from a solution containing at least one of sodium and magnesium, and potassium, and further as an adsorbent for removing potassium from at least one of biological fluids, blood products, blood, and dialysis fluids.

[0072] The molded article of the present embodiment can be packed into a column and used as a column containing the molded article of the present embodiment in a potassium adsorption method, and further can be used as a potassium adsorption system including the column.

[0073] Next, a method for producing the molded article of this embodiment will be described.

[0074] The method for producing the molded article of this embodiment may be any method as long as the molded article contains an eight-membered ring zeolite and an inorganic binder source and has the above-mentioned configuration.

[0075] A preferred production method includes, for example, a production method having a mixing step of mixing an 8-membered ring zeolite and an inorganic binder source to obtain a mixture, and a molding step of molding the mixture to obtain a molded body.

[0076] In the mixing step, the 8-membered ring zeolite and the inorganic binder source may be mixed uniformly by any method, for example, by mixing using one or more devices selected from the group consisting of a ribbon blender, a kneader, a Nauter mixer, and a mix muller.

[0077] The primary particle diameter and particle diameter D50 of the 8-membered ring zeolite and inorganic binder source subjected to the mixing step, and the primary particle diameter and particle diameter D50 of the 8-membered ring zeolite and inorganic binder contained in the molded body of this embodiment are not particularly limited as long as the above-mentioned molded body can be obtained.

[0078] In the mixing step, it is preferable to mix the 8-membered ring zeolite and the inorganic binder so that the mass of the inorganic binder per 100 parts by weight of the 8-membered ring zeolite (anhydrous equivalent mass) is 10 parts by weight or more, 15 parts by weight or more, or 20 parts by weight or more, and 40 parts by weight or less, 30 parts by weight or less, or 25 parts by weight or less.

[0079] The inorganic binder source may be a compound that becomes a compound containing silicon (Si) and oxygen (O), preferably a compound containing silica (SiO2), more preferably a compound that becomes silica when fired, or a compound that becomes a compound containing zirconium (Zr) and oxygen (O), preferably a compound containing zirconia (ZrO2), more preferably zirconia, and functions as an inorganic binder. Preferably, the inorganic binder source is at least one selected from the group consisting of silica sol, colloidal silica, wet process silica, dry process silica, dry process zirconia, wet process zirconia, zirconia sol, zirconium hydroxide, zirconium carbonate, ammonium zirconium carbonate, zirconium oxynitrate, zirconium oxychloride, zirconium oxysulfate, zirconium acetate, and zirconium oxyacetate, more preferably, at least one selected from the group consisting of colloidal silica, zirconium acetate, zirconium oxyacetate, wet process zirconia, zirconia sol, and zirconium hydroxide, and even more preferably, at least one of colloidal silica and zirconia sol. Specific examples of colloidal silica include sodium ion stabilized colloidal silica and ammonium ion stabilized colloidal silica. The inorganic binder source may be in the form of a solid, a slurry, a colloidal solution, or an aqueous solution containing the above-mentioned compound.

[0080] In the mixing step, a molding aid may be mixed as necessary. The molding aid is a substance that improves moldability, and the use of the molding aid makes it easier to control the pore structure of the molded body. Examples of the molding aid include one or more selected from the group consisting of cellulose, alcohol, lignin, starch, and guar gum. Since it is easy to handle, the molding aid is preferably at least one of cellulose and alcohol. Examples of the cellulose include one or more selected from the group consisting of crystalline cellulose, hydroxypropyl methylcellulose, and sodium carboxymethylcellulose (CMC). Examples of the alcohol include at least one of polyvinyl alcohol and ethylene glycol.

[0081] The amount of the molding aid is preferably 1 part by mass or more, or 2 parts by mass or more, and 5 parts by mass or less, or 4 parts by mass or less, based on 100 parts by mass of the zeolite (weight calculated as anhydrous).

[0082] In the molding step, the mixture obtained in the mixing step is molded into a desired shape. Any molding method can be used as long as it can produce a desired shape. Examples of molding methods include extrusion for cylindrical molded bodies, and at least one of rolling granulation and stirring granulation for bead-shaped molded bodies.

[0083] When producing a molded product having an average aspect ratio of more than 1.55, a molding method capable of molding into a cylindrical shape is preferable, and molding by extrusion is more preferable, because it is easy to control the short and long diameters of the molded product. A specific method of molding by extrusion is a method of molding the mixture obtained by the above mixing step into a cylindrical shape having a diameter of 0.1 mm to 10.0 mm using a general extruder (for example, product name: MG-55-1, manufactured by Dalton Co., Ltd.). The average aspect ratio tends to increase as the diameter of the mixture extruded is reduced.

[0084] When producing a compact having an average aspect ratio of 1.55 or less, the molding step is preferably a molding method capable of molding into a nearly spherical or spherical shape, and molding by at least one of a rolling granulation method and an agitation granulation method is more preferable, since it is easy to reduce the average aspect ratio. As an agitation granulation method, a method in which the mixture obtained by the above mixing step is made into a bead-like compact using a general agitation granulation device (for example, product name: FM Mixer (FM5), manufactured by Nippon Coke & Engineering Co., Ltd.) can be mentioned.

[0085] The method for producing the molded body of this embodiment may include a firing step of heat-treating the molded body as necessary. The firing step can increase the strength of the molded body. The firing conditions are arbitrary as long as at least a part of the inorganic binder source is melted and fused to the 8-membered ring zeolite, and examples of the firing conditions include firing at 500°C to 900°C for 2 hours to 4 hours. The firing atmosphere may be an oxidizing atmosphere, such as air. EXAMPLES

[0086] The present disclosure will be described in more detail below with reference to examples, but the present disclosure is not limited to these examples. <Simulated adsorption evaluation> The potassium adsorption performance of the measurement sample was evaluated using a simulated dialysis fluid.

[0087] That is, an aqueous solution containing KCl, NaCl, MgCl2, and CaCl2 and having the following composition was prepared as a potassium solution to serve as a simulated dialysis solution.

[0088] K: 1.0mEq / L Na: 132.0 mEq / L Magnesium: 0.5 mEq / L Ca: 3.5 mEq / L 2.5 mL of the measurement sample was packed into a glass column having an inner diameter of 8.4 mm, and the simulated dialysis fluid was passed through the glass column at a flow rate of 100 mL / min.

[0089] A total of 500 mL of the simulated dialysis fluid discharged from the glass column was collected in 100 mL increments from the start of discharge, and each was diluted 10-fold with pure water to prepare a measurement solution.

[0090] The concentrations of potassium, calcium, and magnesium in the test solution obtained were measured by ICP atomic emission spectrometry using an ICP-AES device (product name: OPTIMA3000DV, manufactured by PERKIN-ELMER), and the potassium removal rate, calcium removal rate, and magnesium removal rate were calculated from the above-mentioned formulas (1) and (2), respectively.

[0091] Prior to the simulated adsorption evaluation, the measurement sample was pretreated by mixing it with 1 L of an aqueous sodium chloride solution with a NaCl concentration of 10 mass % and then washing it with 1.5 L of pure water. <Aluminum elution evaluation> The aluminum elution of the measurement sample was evaluated by the following method.

[0092] That is, 1 mL of the measurement sample was mixed with 10 mL of pure water, and then the mixture was shaken at 37°C for 6 hours at 1.0±0.5 Hz. After shaking, the supernatant was filtered through a membrane filter to obtain a measurement solution. The aluminum content of the measurement solution was measured by ICP-AES (product name: OPTIMA3000DV, manufactured by PERKIN-ELMER) using ICP-AES, and this was taken as the amount of aluminum eluted.

[0093] Prior to the evaluation of aluminum elution, the measurement sample was pretreated by mixing it with 1 L of an aqueous sodium chloride solution with a NaCl concentration of 10 mass % and then washing it with 1.5 L of pure water. <Measurement of pore diameter and pore volume> The pore volume and pore diameter of the measurement sample were measured using a mercury porosimeter (apparatus name: Autopore 9510, manufactured by Micromeritics) by the mercury intrusion method in accordance with JIS Z 1655. The specific measurement conditions for the porosity and pore diameter were as follows.

[0094] Sample weight: 0.10g Mercury introduction pressure: 601.6psia~36,098.1psia (4.1MPa~248.9MPa) Measuring pore diameter: 5nm~300nm Cell used: Pressed volume 1.1cc glass cell Mercury surface tension: 480dyn Mercury contact angle: 130° Pretreatment conditions: Degassing in air at 110℃ for 1 hour or more <Measurement of particle size distribution> The particle size distribution of the measurement sample was measured by the laser diffraction / scattering method. A general particle size distribution measuring device (device name: MT-3100II, manufactured by Microtrack Bell) was used for the measurement. The measurement conditions were as follows:

[0095] Pretreatment: Dry in air at 110℃ for 1 hour Measurement range: 0.7 to 1000 μm Transparency: Transparent Shape: Non-spherical Refractive index: 1.66 Atmosphere: Air (dry) Solvent refractive index: 1 Example 1 FER type zeolite (product name: HSZ (registered trademark)-720KOA, manufactured by Tosoh Corporation, SiO2 / Al2O3 ratio: 18, particle size D50: 8.7 μm) 100 parts by mass (anhydrous equivalent mass: 300.0 g), sodium ion stabilized colloidal silica (product name: ST-30, manufactured by Nissan Chemical Industries, SiO2 equivalent Si concentration: 30 mass%, primary particle size: 12 nm) 20 parts by mass (anhydrous equivalent mass: 60.0 g), and sodium type carboxymethylcellulose (product name: Sunrose F-20LC, manufactured by Nippon Paper Industries Co., Ltd.) 4 parts by mass (anhydrous equivalent mass: 12.0 g) were mixed by stirring for 5 minutes using a stirring granulator (product name: FM Mixer (FM5), manufactured by Nippon Coke and Engineering Co., Ltd.). 105.4 g of pure water was added to the mixture and stirred for another 5 minutes. After that, it was dried overnight at 100°C in an air atmosphere, and then classified using a low-tap type sieve shaker (product name: IIDA SHAVE SHAKER, manufactured by Iida Manufacturing Co., Ltd.) under conditions of an impact frequency of 165 rpm, a rotation speed of 290 rpm, and a processing time of 5 minutes, and further passed through a sieve with a mesh size of 300 μm, and the molded bodies deposited on a sieve with a mesh size of 180 μm were collected. The collected molded bodies were fired in an air atmosphere at 600°C for 2 hours to obtain bead-like molded bodies containing FER-type zeolite (8-membered ring zeolite) and silica (silica binder).

[0096] 500.0 g of a 10 mass % NaCl aqueous solution was passed through the bead-like molded body to carry out ion exchange, with the cation type being Na, to obtain the molded body of this example.

[0097] Example 2 The molded body of this example was obtained in the same manner as in Example 1, except that the molded body that passed through a sieve with 425 μm openings and accumulated on a sieve with 300 μm openings was collected.

[0098] Example 3 The molded bodies of this example were obtained in the same manner as in Example 1, except that the mixture was mixed in a mixer (Hibismix, manufactured by Primix) for 60 minutes, then molded into 0.5 mm cylindrical shapes using an extruder (product name: MG-55-1, manufactured by Dalton), dried, and then crushed using a particle sizer (product name: FXB-3, manufactured by Fuji Paudal) at a hammer rotation speed of 15 Hz, and the molded bodies passed through a sieve with 425 μm openings and accumulated on a sieve with 300 μm openings were collected.

[0099] Example 4 The molded body of this example was obtained in the same manner as in Example 1, except that ammonium ion stabilized colloidal silica (product name: ST-N-30G, manufactured by Nissan Chemical Industries, Ltd., Si concentration calculated as SiO: 30 mass%, primary particle size: 12.5 nm±2.5 nm) was used instead of sodium ion stabilized colloidal silica.

[0100] Example 5 The molded body of this example was obtained in the same manner as in Example 1, except that ammonium ion stabilized colloidal silica (product name: ST-N-30G, manufactured by Nissan Chemical Industries, Ltd., Si concentration converted to SiO2: 30 mass%, primary particle size: 12.5 nm ± 2.5 nm) was used instead of sodium ion stabilized colloidal silica, and the molded body passed through a sieve with a mesh size of 425 μm and accumulated on a sieve with a mesh size of 300 μm was collected.

[0101] Example 6 The molded body of this example was obtained in the same manner as in Example 1, except that the zeolite used was FER-type zeolite (product name: HSZ (registered trademark))-720NHA, manufactured by Tosoh Corporation, SiO2 / Al2O3 ratio: 18, particle size D50: 10.9 μm) which was acid-treated with 1 mol / L hydrochloric acid to change the cation type to H-type, and that ammonium ion-stabilized colloidal silica (product name: ST-N-30G, manufactured by Nissan Chemical Industries, Ltd., Si concentration converted to SiO2: 30 mass%, primary particle size: 12.5 nm ± 2.5 nm) was used instead of sodium ion-stabilized colloidal silica.

[0102] Example 7 The molded product of this example was obtained in the same manner as in Example 6, except that the molded products that had passed through a sieve with 425 μm openings and accumulated on a sieve with 300 μm openings were collected.

[0103] Example 8 100 parts by mass (mass in anhydrous equivalent: 300.0 g) of FER type zeolite (product name: HSZ (registered trademark)-720KOA, manufactured by Tosoh Corporation; SiO2 / Al2O3 ratio: 18; particle size D50: 8.7 μm), 20 parts by mass (mass in anhydrous equivalent: 60.0 g) of zirconia binder (product name: Nanouse ZR, manufactured by Nissan Chemical Industries, Zr concentration converted into ZrO2: 40% by mass; primary particle size: 90 nm), and 4 parts by mass (mass in anhydrous equivalent: 12.0 g) of sodium type carboxymethylcellulose (product name: Sunrose F-20LC, manufactured by Nippon Paper Industries Co., Ltd.) were mixed for 60 minutes in a mixer (Hibismix, manufactured by Primix Corporation). 252.5 g of pure water was added to the mixture, and the mixture was stirred for another 5 minutes. The mixture was then molded into a cylindrical shape with a diameter of 0.3 mm using an extruder (product name: MG-55-1, manufactured by Dalton Co., Ltd.), dried overnight at 100°C in an air atmosphere, and pulverized at a hammer rotation speed of 15 Hz using a granulator (product name: FXB-3, manufactured by Fuji Paudal Co., Ltd.) to obtain a molded body. The obtained molded body was classified using a low-tap type sieve shaker (product name: IIDA SHAVE SHAKER, manufactured by Iida Seisakusho Co., Ltd.) under conditions of an impact speed of 165 rpm, a rotation speed of 290 rpm, and a processing time of 5 minutes, and the molded body that passed through a sieve with a mesh size of 710 μm and accumulated on a sieve with a mesh size of 180 μm was collected. The collected molded body was fired at 600°C for 2 hours in an air atmosphere to obtain a cylindrical molded body containing FER type zeolite (8-membered ring zeolite) and zirconia (zirconia binder).

[0104] 500.0 g of a 10 mass % NaCl aqueous solution was passed through the cylindrical molded body to carry out ion exchange to obtain a cation type of Na, thereby producing the molded body of this example.

[0105] Example 9 The molded body of this example was obtained in the same manner as in Example 8, except that 20 parts by mass (mass in anhydrous equivalent: 60.0 g) of sodium ion-stabilized colloidal silica (product name: SH-3, manufactured by Fuso Chemical Co., Ltd., Si concentration calculated as SiO2: 34.4 mass%, primary particle size: 35.6 nm) was used instead of the zirconia binder, 174.0 g of pure water was added to the mixture, and the recovered molded body was fired at 800°C for 2 hours in an air atmosphere.

[0106] Example 10 A molded body of this example was obtained in the same manner as in Example 9, except that 10 parts by mass (mass in anhydrous equivalent: 30.0 g) of sodium ion-stabilized colloidal silica (product name: SH-3, manufactured by Fuso Chemical Co., Ltd., Si concentration calculated as SiO2: 34.4 mass%, primary particle size: 35.6 nm) was mixed, 230.1 g of pure water was added to the mixture, and the mixture was molded into a cylindrical shape with a diameter of 0.5 mm using an extruder.

[0107] Example 11 The molded body of this example was obtained in the same manner as in Example 9, except that 15 parts by mass (mass in terms of anhydrous: 45.0 g) of sodium ion-stabilized colloidal silica (product name: SH-3, manufactured by Fuso Chemical Co., Ltd., Si concentration calculated as SiO2: 34.4 mass%, primary particle size: 35.6 nm) was mixed, and 63.6 g of pure water was added to the mixture.

[0108] Comparative Example 1 The molded body of this comparative example was obtained in the same manner as in Example 1, except that FAU-type zeolite (product name: HSZ (registered trademark)-320NAA: manufactured by Tosoh Corporation, SiO2 / Al2O3 ratio: 5.7, particle size D50: 6.3 μm) was used as the zeolite.

[0109] Comparative Example 2 A molded body of this comparative example was obtained in the same manner as in Example 1, except that the molded body that passed through a sieve with 1.2 mm openings and accumulated on a sieve with 1.0 mm openings was collected.

[0110] Comparative Example 3 A commercially available FER type zeolite compact (product name: HSZ (registered trademark)-720KOD1C, 1.5 mmφ cylindrical pellets, binder: clay, SiO2 / Al2O3 ratio: 18, particle size D50: (zeolite) 8.7 μm, (binder) 12 μm) was crushed in a mortar, passed through a sieve with 425 μm openings, and then deposited on a sieve with 300 μm openings to obtain a cylindrical pellet compact.

[0111] 500.0 g of a 10 mass % NaCl aqueous solution was passed through the cylindrical pellet molded body to effect ion exchange to obtain a cation type: Na, thereby obtaining a molded body of this comparative example.

[0112] Comparative Example 4 100 parts by mass of MOR type zeolite (product name: HSZ (registered trademark)-620HOA, manufactured by Tosoh Corporation; SiO2 / Al2O3 ratio: 18; particle size D50: 10.1 μm), 20 parts by mass (anhydrous equivalent mass: 60.0 g) of sodium ion stabilized colloidal silica (product name: SH-3, manufactured by Fuso Chemical Co., Ltd.; Si concentration converted into SiO2: 34.4% by mass; primary particle size: 35.6 nm), and 4 parts by mass (anhydrous equivalent mass: 12.0 g) of sodium type carboxymethylcellulose (product name: Sunrose F-20LC, manufactured by Nippon Paper Industries Co., Ltd.) were mixed for 60 minutes in a mixer (Hibismix: manufactured by Primix Corporation). 95.1 g of pure water was added to the mixture, and the mixture was stirred for another 5 minutes. The mixture was then molded into a 1.0 mm cylindrical shape using an extruder (product name: MG-55-1, manufactured by Dalton Co., Ltd.), dried overnight at 100°C in an air atmosphere, and crushed at a hammer rotation speed of 15 Hz using a granulator (product name: FXB-3, manufactured by Fuji Paudal Co., Ltd.) to obtain a molded body. The obtained molded body was classified using a low-tap type sieve shaker (product name: IIDA SHAVE SHAKER, manufactured by Iida Seisakusho Co., Ltd.) under conditions of an impact speed of 165 rpm, a rotation speed of 290 rpm, and a processing time of 5 minutes, and the molded body that passed through a sieve with a mesh size of 1.2 mm and accumulated on a sieve with a mesh size of 1.0 mm was collected. The collected molded body was fired at 600°C for 2 hours in an air atmosphere to obtain a cylindrical molded body containing MOR type zeolite (8-membered ring zeolite) and silica (silica binder).

[0113] 500.0 g of a 10 mass % NaCl aqueous solution was passed through the cylindrical molded body to carry out ion exchange to obtain a cation type of Na, thereby producing the molded body of this example.

[0114] The evaluation results of the examples and comparative examples are shown in the table below.

[0115] [Table 1]

[0116] [Table 2] [Industrial Applicability]

[0117] The molded article of the present disclosure has a pore size distribution and particle size useful for adsorbing and removing potassium ions, and can therefore be usefully used for adsorbing potassium contained in a solution, preferably for adsorbing potassium from potassium ion-containing effluent generated by artificial dialysis.

Claims

1. A molded body comprising a zeolite having an 8-membered oxygen ring structure, and at least one of a silica binder and a zirconia binder, wherein the ratio of a cumulative pore volume having a pore diameter of 10 nm or more and 100 nm or less to a cumulative pore volume having a pore diameter of 5 nm or more and 300 nm or less is 25 vol% or more and 70 vol% or less, the average aspect ratio is more than 1.55 and 2.70 or less, the pore diameter at which the cumulative pore volume is 50 vol% to the cumulative pore volume having a pore diameter of 5 nm or more and 300 nm or less is 75 nm or more and 160 nm or less, and at least one of the silica binder and the zirconia binder has a primary particle diameter of 10 nm or more and 150 nm or less.

2. The cumulative pore area of ​​the pores having a diameter of 5 nm or more and 300 nm or less is 10.0 m 2 / g or more 35.0m 2 The molded article according to claim 1, wherein the molecular weight is 1 / g or less.

3. The molded body according to claim 1 or 2, wherein the zeolite is at least one of a cation type: Na (sodium) zeolite and a cation type: H (proton) zeolite.

4. 3. The molded article according to claim 1, wherein the ratio of a cumulative pore volume having a pore diameter of 5 nm or more and 10 nm or less to a cumulative pore volume having a pore diameter of 5 nm or more and 300 nm or less is 0.1 vol % or more and 5.0 vol % or less.

5. 3. The molded article according to claim 1, wherein the cumulative pore volume of pores having a diameter of 5 nm or more and 300 nm or less is 0.35 mL / g or more and 0.60 mL / g or less.

6. 3. The molded article according to claim 1, wherein the zeolite has one or more framework structures selected from the group consisting of a FER structure, a HEU structure, a YFI structure, a MAZ structure, a CHA structure, and a MOR structure.

7. The molar ratio of silica to alumina in the zeolite (SiO 2 / Al 2 O 3 The molded article according to claim 1 or 2, wherein the ratio (ratio) is 3 or more and 100 or less.

Citation Information

Patent Citations

  • Potassium adsorbent for biological fluid and potassium adsorbent for dialysate

    JP2023125494A

  • Method of adsorption of ions from a dialysis fluid

    US20150297815A1